Postharvest processing of custard apple (Annona squamosa L.) - a review - Soni, Narotam; Mudgal, V D; Champawt , P S (Journal of Postharvest Technology, 2021)
As the pandemic conditions of 2020, the demand of immunity booster and highly nutritious products has led to increase in consumption of fruits  and their processed products. Custard Apple (Annona squamosa L.) is good source of bioactive compounds along with high sensory properties.  Although custard apple is antioxidant, anti-diabetic, hepato-protective, cytotoxic, genotoxic, antitumor and anti-lice agent but still it is counted as  underutilized fruit, due to less processing technologies available throughout the world. In the last two decades this fruit has attracted researchers  with challenges as preservation of whole fruit and pulp, de-pulping of custard apple and maintaining nutritional value for custard apple during  processing. Minimally processed products from the fruit may be a convenient option for households, farmers and foodservice providers.  Processed products of fruit will inhibit the quality deterioration, browning of pulp and fruit, microbial contamination and increase in shelf life as  well as cost of processed products. The present chapter possesses information related to de-pulping, utilization and value added or processed  products from custard apple.
Keywords: Custard apple pulp; de-pulping; processed product; value addition